Sulfobutylether-β-cyclodextrin as a chiral selector for separation of amino acids and dipeptides in chromatography - Kučerová, Gabriela; Procházková, Hana; Kalíková, Květa; Tesařová, Eva (Journal of chromatography. A, 2016)
Various amino acids, dipeptides and their isomers were (enantio)separated using sulfobutylether-β-cyclodextrin as a chiral selector. Two different approaches were employed: first, dynamic coating of sulfobutylether-β-cyclodextrin onto a strong anion-exchange stationary phase and, second, use of sulfobutylether-β-cyclodextrin as a mobile phase additive in a separation system with a C18 column. Measurements were carried out using RP-HPLC and hydrophilic interaction liquid chromatography. Mobile phases composed of organic modifier (methanol) and four different aqueous parts: (i) deionized water, (ii) an aqueous solution of formic acid (pH 2.1), (iii) ammonium acetate buffer (pH 4.7), and (iv) ammonium acetate buffer (pH 8.8) in various volume ratios. Under these separation conditions, out of 23 chiral analytes, 9 were baseline enantio-resolved and 7 were partially separated. Of 9 mixtures of dipeptide isomers, 8 were baseline-separated. Sulfobutylether-β-cyclodextrin proved to be suitable for the separation of chiral and also achiral analytes. The use of sulfobutylether-β-cyclodextrin as a dynamic coating agent or as a mobile phase additive depends on the particular chromatographic system and analytes of interest.
Keywords: dipeptidy; Chromatography, High Pressure Liquid; beta-Cyclodextrins; Sulfobutylether-β-cyclodextrin; Dynamic coating; stereoizomerie; pufry; Dipeptides; formiáty; Chiral selector; Stereoisomerism; aminokyseliny; Amino Acids; acetáty; Buffers; Mobile phase additive; beta-cyklodextriny; HPLC; voda; Formates; Water; Acetates; indikátory a reagencie; vysokoúčinná kapalinová chromatografie; Indicators and Reagents